(untitled) (European Journal of Marketing and Economics, 2026)
This study investigates brand love dynamics using the Disney brand as a case study across Portuguese and Brazilian consumers, extending existing theory to under-researched Lusophone markets. It pursues three specific research objectives: (RO1) to empirically test whether Disney qualifies as a brand love; (RO2) to examine sociodemographic differences in brand love; and (RO3) to identify key antecedents of brand love. Data were collected via an online questionnaire from a non-probabilistic convenience sample of Portuguese and Brazilian adults (N = 310) using snowball sampling through social media. Analysis included factor analysis, non-parametric tests, and multiple regression. Results confirm Disney qualifies as a loved brand, reveal nationality (Brazilian > Portuguese) and age effects, and identify satisfaction and self-expressiveness as dominant antecedents, with trust, quality significant and storytelling non-significant. Findings advance brand love theory through multi-antecedent testing within a single iconic brand and cross-cultural insights from Lusophone markets. Practically, they guide experiential brand managers toward satisfaction, and self-expression, focused strategies for emotional differentiation in Portuguese/Brazilian contexts.